1979
DOI: 10.1007/bf02533531
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of [14C] choline and incorporation into lung phospholipid by the isolated perfused rat lung

Abstract: We have used the isolated perfused lung (IPL) preparation from the rat to determine whether uptake of choline from the vascular compartment could limit the rate of synthesis of phosphatidyl-choline (PC). The uptake of choline was rapid and did not saturate at a concentration of 10 mM. The rate of incorporation of choline into phospholipid was saturated above 0.1 mM choline. Whereas, uptake and incorporation were depressed at 4 C, uptake was neither dependent on the extracellular sodium concentration nor inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…(CDP-choline) pathway, which requires the circulating chohne to be transported into the lung by the alveolar epithelium. It has been suggested that this trans-c~llular t~sport process may be rate-limiting for the biosynthesis of pulmonary PC (70,71). In addition, alveolar type II epithelial cells have developed two types of "active" chol~ne transport mechanisms to regulate the pulmonary chohne content (68): The first is a high-affinity, Na+-depend~nt system (K m of 1.5 JlM: Kj of 1.7 JlM for HC-3)…”
Section: Systems For Choline Transportmentioning
confidence: 99%
“…(CDP-choline) pathway, which requires the circulating chohne to be transported into the lung by the alveolar epithelium. It has been suggested that this trans-c~llular t~sport process may be rate-limiting for the biosynthesis of pulmonary PC (70,71). In addition, alveolar type II epithelial cells have developed two types of "active" chol~ne transport mechanisms to regulate the pulmonary chohne content (68): The first is a high-affinity, Na+-depend~nt system (K m of 1.5 JlM: Kj of 1.7 JlM for HC-3)…”
Section: Systems For Choline Transportmentioning
confidence: 99%
“…Indeed, previous studies have suggested that choline transport into ATII cells could be the rate-limiting step in pulmonary PC biosynthesis. 8,9) Moreover, we demonstrated that choline transporter-like protein 1 (CTL1) plays a role in supplying choline to ATII cells for PC biosynthesis. 10) Although little is known about other mechanisms, CTL1-mediated choline transport is considered to be the first step of CDP-choline pathway.…”
mentioning
confidence: 99%
“…In the present experiments we used [3H]-choline as the phospholipid precursor, as we had found that about 90% of the label subsequently detected in the lung was as phosphatidylcholine (Johnson et al, 1979), the principal phospholipid in surfactant. We chose to lavage the lungs 5 h after the infusion of choline, for at this time PLalvsp.act is about 60% of maximal labelling which occurs at between 8 and 12 h (Power et al, 1986).…”
Section: Validation Of Methodsmentioning
confidence: 99%